Comparison of interlimb coordination during soccer instep kicking between elite and amateur players - Zhou, Z.; Gao, Z.; Li, F.; Wang, D.; Wang, Y.; Fekete, G.; Gu, Y. (European Journal of Sport Science, 2025)
This study investigates how interlimb joint coordination influences foot speed during soccer instep kicking, using continuous relative phase (CRP) as a quantitative method. The sample includes 15 elite and 15 amateur players to examine potential differences in coordination patterns and their impact on performance. Specifically, we focused on the coordination between hip, knee, and ankle joints in the forefoot-back kicking motion. Results indicated that elite players exhibited significantly higher hip-knee CRP in the coronal plane during 62%-81% of movement duration (p = 0.015) and higher knee-ankle CRP in the vertical plane during 78%-100% (p = 0.013). Moreover, elite players had significantly greater hip-knee mean absolute relative phase (MARP) and deviation phase (DP) in the coronal plane (p < 0.001), as well as increased knee-ankle DP (p = 0.04). In the horizontal plane, hip-knee MARP was also greater in the elite players compared to amateurs (p < 0.001). Further analysis revealed a significant negative correlation between hip-knee CRP and foot velocity in the sagittal plane (R = -0.66, p < 0.001), whereas a significant positive correlation was observed between knee-ankle CRP and foot velocity in the horizontal plane (R = 0.56, p = 0.002). These findings suggest that elite players have superior joint coordination, which contributes to a faster foot velocity at the moment of ball impact. Understanding these coordination patterns provides valuable insights into optimizing kicking techniques. The findings of this study suggest that joint coordination may play an important role in enhancing kicking foot speed, which could inform future training approaches aimed at improving soccer performance.